2016
DOI: 10.1080/21655979.2016.1227609
|View full text |Cite
|
Sign up to set email alerts
|

Non-Fourier based thermal-mechanical tissue damage prediction for thermal ablation

Abstract: Prediction of tissue damage under thermal loads plays important role for thermal ablation planning. A new methodology is presented in this paper by combing non-Fourier bio-heat transfer, constitutive elastic mechanics as well as non-rigid motion of dynamics to predict and analyze thermal distribution, thermal-induced mechanical deformation and thermal-mechanical damage of soft tissues under thermal loads. Simulations and comparison analysis demonstrate that the proposed methodology based on the non-Fourier bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Existing experimental studies available in literature have highlighted that the exposure of biological tissue to elevated temperatures (> 50 o C) during thermal ablative procedures can result in varying degree of mechanical deformation (including both expansion and contraction) within the tissue [24][25][26][27][28][29][30][31][32][33][34][35][36]. Several computational studies have also been reported to capture such mechanical deformations, but mainly limited to only thermal expansion [37][38][39][40][41][42][43]. Importantly, ignorance of the impact of tissue contraction/shrinkage during thermal ablative procedures has resulted in significant underestimation of the predicted ablation volume (see, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing experimental studies available in literature have highlighted that the exposure of biological tissue to elevated temperatures (> 50 o C) during thermal ablative procedures can result in varying degree of mechanical deformation (including both expansion and contraction) within the tissue [24][25][26][27][28][29][30][31][32][33][34][35][36]. Several computational studies have also been reported to capture such mechanical deformations, but mainly limited to only thermal expansion [37][38][39][40][41][42][43]. Importantly, ignorance of the impact of tissue contraction/shrinkage during thermal ablative procedures has resulted in significant underestimation of the predicted ablation volume (see, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Both contractions and expansions have been noticed and reported in the literature in the previous clinical studies of thermal ablation (Merkle et al 2005, Ganguli et al 2008, Brace et al 2010, Sommer et al 2013, Rossmann et al 2013, Ziemlewicz et al 2014, Moreland et al 2014, Farina et al 2014, Liu and Brace 2014, Lee et al 2016, Amabile et al 2017, Lopresto et al 2018, Farina et al 2018. At the same time, very few numerical studies are available in literature that incorporate systematically the thermo-elastic wave equation for capturing mechanical deformations induced by thermal expansion during thermal ablative procedures (Keangin et al 2011, Li et al 2014, Chaichanyut and Tungjitkusolmun 2016, Li et al 2017, Keangin and Rattanadecho 2018, Wongchadakul et al 2018, Karaki et al 2018. Moreover, tissue contraction induced by protein denaturation at elevated temperatures during thermal ablation procedures have been clearly missing in such numerical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, non-linear couplings of the heat equation with approximations of the radiative heat transfer equation are often employed. Various authors have investigated the Cattaneo equation and the effect of the delay parameter on the speed of propagation, also in the complex situation of thermoablation (see, e.g., [1,2,3,4,5]). In real life applications, these models often depend on various unknown parameters.…”
Section: Introductionmentioning
confidence: 99%